Mental Health Interventions for First Nations, Inuit, and Métis Peoples in Canada: A Systematic Review - Graham, Simon; Stelkia, Krista; Wieman, Cornelia; Adams, Evan (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2021)
Higher rates of anxiety, depression, and attempted suicide are reported among First Nations, Inuit, and Métis people compared with non-Indigenous people in Canada. This systematic review summarises the key components of mental health interventions among Indigenous Peoples in Canada. We searched MEDLINE, PubMed, PsycINFO, and Web of Science between January 1,1970, and August 30, 2019. Studies needed to be an intervention addressing suicide, depression, or anxiety. There were 14 studies: 8 quantitative, 2 qualitative, and 4 mixed methods. By geographical location, 5 were urban, 5 non-urban, and 4 included multiple areas. Beneficial interventions included ceremony, being on the land, engaging in traditional food gathering, culturally grounded indoor and outdoor activities, and the sharing of Indigenous knowledge by Elders.